Pengaruh Struktur Kepemilikan Saham dan Ukuran Perusahaan terhadap Pengungkapan Corporate Social Responsibility (CSR) Pada Perusahaan Manufaktur yang Terdaftar Di BEI - Dedy Trisetiawan; Hamzah Fansuri Yusuf; Wiwik Fitria Ningsih (Institut Teknologi dan Sains Mandala, 2022)
This study was conducted to determine the factors that influence the disclosure of Corporate Social Responsibility. This type of research is a quantitative research. The population used in this study were all manufacturing companies in the food and beverage -sector listed on the Indonesia Stock Exchange from 2015 to 2019. The sample used in this study was collected based on data obtained from the company's annual report using the purposive sampling method. The data collection method in this study used the documentation study method and data analysis using the SPSS 20 (Statistical Package for the Social Sciences) program, by performing descriptive statistical analysis and multiple linear regression analysis, R test, t test, and F test. data has been obtained that institutional ownership structure, managerial ownership structure has no significant effect on the disclosure of Corporate Social Responsibility, while the size of the company has a significant effect on the disclosure of Corporate Social Responsibility. Simultaneously, institutional ownership structure, managerial ownership structure, and firm size have a significant effect on the disclosure of Corporate Social Responsibility.